Zawód specjalisty ds. rachunkowości zarządczej w perspektywie etycznej - Kalinowska, Katarzyna; Kalinowski, Marcin (Annales. Etyka w Życiu Gospodarczym, 2014)
Increasing market competitiveness has brought about changes in enterprisemanagement. There was a demand for an increase in the quality and quantityof information needed for operational and strategic management procedures.With the increasing demand for the desired cross-section of information necessaryfor an accounting system, in addition to the financial accounting responsiblefor generating financial information, management accounting was established.The purpose of this article is to seek answers to the question about howthe professional ethics of management accountants are related to the natureand specifics of carrying out their professional duties.